Appreciating my core values to more fully appreciate others: My livingeducational-theory as a peace education researcher-practitioner - Joakim Arnøy (Educational Journal of Living Theories)
This article presents an inwards search for educational values at the core of my conduct and character as a peace education researcher and practitioner. To help me locate, and formulate my driving, educational values, I relate how I came to prefer non-formal education as my preferred learning format. Among the reasons is how the format encourages people to see each other, as well as the uniqueness every participant brings to the group. I bring this together to conceptualise appreciative values, by which I mean that each person’s contribution is valued, and recognised for its potential power to contribute to social change in the educational setting and beyond. This concept of appreciative values is the foundation of my livingeducational-theory. To validate my improvement with regards to my values, I look to feedback forms of educational activities I have facilitated in the past. Through this, I find evidence that I have grown more into the role of an educational facilitator, and that my way of living according to appreciative values has had an influence on others I have come across. However, I also identify a gap in my demeanour, by which I act in living contradiction with my values. Acknowledging the potential for improvement, I engage in reflection with a work colleague to try to make use of that gap as a learning opportunity.